Formulasi Sediaan Lip Cream Dari Ekstrak Etanol Daun Bayam Merah (Amaranthus Tricolor L.) Sebagai Pewarna Alami Bibir - Rizal, Rosiana; Salman, Salman; Putri, Dini Yulanda (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2025)
Cosmetics are used to beautify themselves with the intention of adding to their add attraction to be more liked. One of the cosmetics favored by women is lip color, such as lip cream. The application of color is very important to improve the quality of lip cream preparation. A plant that has a dye, namely red spinach (Amarantus tricolor L.) in the form of betacyanin at 0,085%. Apart from being a dye, red spinach also has antioxidant activity which can be seen at the IC50 value 29,76 µg/ml (>50 µg/ml). The purpose of this study was to determine whether the ethanol extract of red spinach leave with concentration of 5%, 10% and 15% could be formulated in lip cream preparations according to the requirements of the evaluation of the preparation (pH test, homogeneity, spreadability, adhesion, stability and irritation test) and to determine the effect of the concentration of red spinach ethanol extract in the preparation. The result showed that the lip cream preparation F0 (without extract), F1 (5%), F2 (10%) and F3 (15%) were stable and evenly dispersed during unform storage. The difference in the concentration of the ethanol extract of red spinach leaves affects the color of the preparation, namely white (F0), pink (F1), brick red (F2) and dark red (F3). The higher the concentration of the extract, the darker the color and the more acidic the pH of the preparation. In the evaluation the preparations, it was found that the pH test was according to the skin range, adhesion and spreadability met the requirements and was not irritating. The result of the preference test found that the best preparation was F2 as much as 28%.